2008
DOI: 10.1177/1352458508090663
|View full text |Cite
|
Sign up to set email alerts
|

Factors in the rising prevalence of multiple sclerosis in the north-east of Ireland

Abstract: Northern Ireland continues to have a rising prevalence of MS. The increase in incidence suggests a true increase in the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 36 publications
5
33
1
Order By: Relevance
“…The increasing temporal trend with an overall female to male ratio (1.9) of MS risk for entire study period concurs with the findings of several other studies conducted across the globe including Canada (3.2) [3] , French West Indies (2.0) [37] , Isfahan, Iran (3.3) [10] , Japan (3.4) [38] , South-East Wales, UK (4.3) [35] , Ireland (2.0) [39] , Finland (2.2) [36] , New Zealand (2.7) [40] , Sweden (2.7) [41,42] , Denmark (2.0) [43] , Oslo, Norway (2.3) [44] , Spain (4.0) [7] and other European countries (3.4) [45] . A meta-regression analysis of most of the aforementioned studies highlighted the rise in MS incidence and prevalence over recent 3-6 decades mainly due to the increased burden of relapsing-remitting MS in females [8] .…”
Section: Discussionsupporting
confidence: 90%
“…The increasing temporal trend with an overall female to male ratio (1.9) of MS risk for entire study period concurs with the findings of several other studies conducted across the globe including Canada (3.2) [3] , French West Indies (2.0) [37] , Isfahan, Iran (3.3) [10] , Japan (3.4) [38] , South-East Wales, UK (4.3) [35] , Ireland (2.0) [39] , Finland (2.2) [36] , New Zealand (2.7) [40] , Sweden (2.7) [41,42] , Denmark (2.0) [43] , Oslo, Norway (2.3) [44] , Spain (4.0) [7] and other European countries (3.4) [45] . A meta-regression analysis of most of the aforementioned studies highlighted the rise in MS incidence and prevalence over recent 3-6 decades mainly due to the increased burden of relapsing-remitting MS in females [8] .…”
Section: Discussionsupporting
confidence: 90%
“…Other explanatory factors for an increasing MS incidence are largely unknown but changes in environmental factors have been suggested [28,29]. In line with our study, several other studies reported that the increasing MS incidence was mostly attributable to an increase among women [23,25,27,30,31,32,33,34]. Solid evidence for the shift in F:M sex ratio is yet unknown but perhaps changing lifestyle factors among women, e.g.…”
Section: Discussionsupporting
confidence: 90%
“…The sample comprised of 202(31.9%) male, and 431(68.1%) females. (20)(21)(22)(23)(24), While (34.1%) of the respondents Aged between (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), While (18.8%) of the respondents Aged more than 35. Table (3) that (34.4%) of the respondents belong to the eastern region, while (33.5%) of them belong to the western region, (20.4%) of them belong to the Central Region, and (7.3%) of them belong to the southern district.…”
Section: Methodology:-mentioning
confidence: 95%